Towards a virtual test framework to predict residual compressive strength after lightning strikes - Millen, Scott L. J.; Xu, Xiaodong; Mukhopadhyay, Supratik; Wisnom, Michael R.; Murphy, Adrian (Elsevier, 2023)
A novel integrated modelling framework is proposed as a set of coupled virtual tests to predict the residual compressive strength of carbon/epoxy composites after a lightning strike. Sequentially-coupled thermal-electric and thermo-mechanical models were combined with Compression After Lightning Strike (CAL) analyses, considering both thermal and mechanical lightning strike damage. The predicted lightning damage was validated using experimental images and X-ray Computed Tomography. Delamination and ply degradation information were mapped to a compression model, with a maximum stress criterion, using python scripts. Experimental data, in which artificial lightning strike and compression testing were performed, was used to assess the predictive capabilities of the framework, considering three lightning strike peak current amplitudes (25, 50, and 75 kA). The framework herein achieved a residual strength prediction within 6% of the experimental values for all peak currents. The relationship between individual lightning damage morphologies (thermal, mechanical and delamination damage) and CAL strength has been numerically established.
Keywords: B. Delamination; B. Thermomechanical; C. Finite Element Analysis (FEA); Compression after Lightning Strikes (CAL)